The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.24187/ecostat.2017.494t.1925
|View full text |Cite
|
Sign up to set email alerts
|

The individual dynamics of wage income in France during the crisis

Abstract: The uncertain nature of future income limits the ability of agents to smooth their consumption over time. Variation in this uncertainty can thus bring about variation in well-being. We study the evolutions of the uncertainty on wage income in France before and over the course of the crisis of 2008 drawing on longitudinal administrative data. Using a non-parametric method, we estimate the magnitude and form of this uncertainty and show that they depend on past wage income. This uncertainty is broken down into w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Intuitively, the effort shock generated by motherhood might be less severe for a highly educated woman because it is partially absorbed by the human capital she has accumulated before her maternity leave. Pora and Wilner (2019) use French administrative data and document the heterogeneity of the consequences of childbirth along the distribution of pre-childbirth wages; their evidence is fully in line with our results. However, the fact that women with low SES are more likely to enter the wage trap does not necessarily imply that they also suffer the higher child penalty overall.…”
Section: Introductionsupporting
confidence: 80%
“…Intuitively, the effort shock generated by motherhood might be less severe for a highly educated woman because it is partially absorbed by the human capital she has accumulated before her maternity leave. Pora and Wilner (2019) use French administrative data and document the heterogeneity of the consequences of childbirth along the distribution of pre-childbirth wages; their evidence is fully in line with our results. However, the fact that women with low SES are more likely to enter the wage trap does not necessarily imply that they also suffer the higher child penalty overall.…”
Section: Introductionsupporting
confidence: 80%
“…In previous work, Angelov et al (2016) ; Chung et al (2017) and Pora and Wilner (2019) concluded that their findings are consistent with household specialization. Angelov et al (2016) and Chung et al (2017) base this on the finding that the within-couple earnings gap increases more after the birth of the first child if the father has a higher earnings potential, while Pora and Wilner (2019) base it on the finding that higher-earning women reduce their labor supply (and subsequently earnings) less after childbirth. Our results from analyses 19 Online appendix table B2 shows results for the three measures of earnings potential discussed in online appendix section B.…”
Section: Discussionmentioning
confidence: 58%
“…The evidence regarding this channel is, however, mixed. Angelov et al (2016) ; Pora and Wilner (2019) and Chung et al (2017) find support for it, while Andresen and Nix (2020) ; Kleven et al (2021) and Rosenbaum (2019) do not. A possible reason for this are differences in relevant institutions regarding for example the possibilities to adjust working hours or to use formal child care for very young children.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations